2021
DOI: 10.33006/ji-kes.v4i2.197
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Covid-19 Knowledge and Anxiety of Pregnant Women During Covid-19 Pandemic

Abstract: AbstrakWanita hamil adalah salah satu kelompok khusus yang berisiko tinggi tertular virus Covid-19.Faktor risiko terbesar untuk mengalami berbagai tekanan psikologis adalah perempuan dan tenaga kesehatan serta populasi rentan seperti ibu hamil. Ketakutan dan kekhawatiran muncul dari bahaya yang memang ada, tetapi banyak juga yang muncul dari kurangnya pengetahuan dan informasi yang salah. Tujuan penelitian ini adalah untuk mengetahui hubungan pengetahuan Covid-19 dengan kecemasan ibu hamil pada saat pandemi Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…This study found that pregnant women with low COVID-19-related knowledge had a higher risk of anxiety than pregnant women with good COVID-19related knowledge. This study finding was in line with a study conducted in Indonesia which stated that there was a significant relationship between knowledge and anxiety in pregnant women during the COVID-19 pandemic [44]. The finding of a study conducted in Wuhan was also in line with this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study found that pregnant women with low COVID-19-related knowledge had a higher risk of anxiety than pregnant women with good COVID-19related knowledge. This study finding was in line with a study conducted in Indonesia which stated that there was a significant relationship between knowledge and anxiety in pregnant women during the COVID-19 pandemic [44]. The finding of a study conducted in Wuhan was also in line with this study.…”
Section: Discussionsupporting
confidence: 91%
“…Pregnant women need to appoint reliable sources of knowledge related to COVID-19 from both online and offline media. In addition, health services also have a role in emphasizing correct information to the public, especially pregnant women, regarding COVID-19-related knowledge [44]. Antenatal care effectively provides information to pregnant women that can improve their understanding of knowledge and maternal health status [47].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, various factors are used to determine whether or not the mother should be vaccinated. According to the research findings of Septiasari, et al (2021), it is critical for healthcare practitioners to offer information about the prevention of COVID-19 during a pregnancy, especially about COVID-19 vaccine (Septiasari & Viandika, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Increased knowledge of pregnant women aids in reducing their negative attitude and increases the preventive measures taken against COVID-19 11 . Knowledge regarding the pandemic was a determining factor for pregnant women to achieve an ideal pregnancy during the COVID-19 pandemic 12 . Adherence to COVID-19 preventive measures among pregnant women is insufficient; hence, studies are recommended to create awareness about COVID-19 through the media and health education 13,14 .…”
Section: Introductionmentioning
confidence: 99%